The effect of cutting interval on nutritive value and in sacco degradability of Klienhovia hospita - Azmi, Mohd Afiq (2016)
Nowadays, many developing countries, with high population growth rates, combined with limited and rapidly diminishing land for food and forage production, have created a need to intensify agricultural production in order to bridge the gap between requirement and supply of food to ensure proper human nutrition. In Malaysia, ruminants are mostly fed with low nutritive value forages. Most of our farmers feed their animals with forages of main diet of low digestibility and also low nutritive values that are sourced from poorly managed pasture. A study was conducted at Ladang 2, University Putra Malaysia, Serdang, Selangor to evaluate the effect of cutting interval on nutritive value and in sacco degradability pattern of Klienhovia hospita for the optimum harvesting age. The experiment consisted of three treatments of one variety of Klienhovia hospita. The fodder trees were sampled at 45 days, 60 days and 75 day cutting interval and used completely randomized design (CRD). The samples were analysed for leaf and stem percentage, dry matter content (DM), neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL), crude protein (CP) and degradation pattern of DM of Klienhovia hospita and highly significant difference (P<0.0001) in DM, NDF, ADF, ADL, and CP were observed at different cutting interval. The result of dry matter percentage (DM) showed highly significant difference at (P<0.0001) for all treatments. As the cutting intervals increase the dry matter percentage also increased. Result showed that dry matter percentage was higher at 75 day cutting interval (30.6%) followed by 60 days cutting interval (28.89%) and 45 days cutting interval (27.33%). The leaves percentage showed highly significant difference at (P<0.0001), where the leaves percentage decrease as the plant grow older due to stem development. The result showed leaf percentage was the highest at 45 days cutting interval (58.66%) followed by 60 days cutting interval (51.21%) and 75 days cutting interval (48.54%). The result for crude protein (CP) showed there were highly significant different at (P<0.0001) among all treatments. Crude protein (CP) was higher at 45 days cutting interval (23.15%) followed by 60 days cutting interval (20.21%) and 75 days cutting interval (19.47%). The result of neutral detergent fiber (NDF) showed there were highly significant difference at (P<0.0001) among all of treatments. The highest of neutral detergent fiber (NDF) was found at 75 days cutting interval (43.95%) followed by 60 days cutting interval (42.04%) and 45 days cutting interval (40.6%). The result for acid detergent fiber (ADF) showed there were highly significant difference at (P<0.0001) among all of the treatments. The result showed that acid detergent fiber (ADF) was highest at 75 days cutting interval (41.6%) compared to 60 days cutting interval (39.26%) and 45 days cutting interval (38.53%). The result for acid detergent lignin (ADL) showed there were highly significant difference at (P<0.0001) among all of the treatment. The result also showed acid detergent lignin was highest at 75 day cutting interval (11.01%) followed by 60 days cutting interval (9.54%) and 45 days cutting interval (9.21%). The result for rumen degradation of Klienhovia hospita show the highest degradation pattern was at 45 days cutting interval. It was observed that 45 days cutting interval was superior in term of crude protein, leaf percentage and rumen degradation. This study also showed the most preferable cutting interval for Klienhovia hospita was at 45 days where the nutrient content was at optimum level.